The Impact of Slavery and Colonialism on the Black Consciousness: Narrative of the Life of Frederick Douglass, The Confessions of Nat Turner, and Incidents in the Life of a Slave Girl - Badawi, Mariam (AUC Knowledge Fountain, 2023)
According to the German author, essayist, and empirical psychologist Karl Philipp Moritz, to be able to analyze someone psychologically, we have to be able to analyze ourselves as one would know oneself better than one would know anyone else. Therefore, he proposed the study of autobiographies to be able to delve into a writer's "innermost soul"; through their knowledge of themselves" (qtd. in Schlumbohm 32). Moreover, "the psychological effect that the ideology of white supremacy and European imperialism, in the form of slavery and colonialism, has had on Africa and her people has never been fully addressed and understood" (Nobles 233). Slave narratives provide insights into the slaves' consciousness and the impact slavery has left on such consciousness as well as the rippling effect it has left in its wake on the slaves' descendants. Thus, to be able to better understand the impact on the Black race in general, for the slaves and their descendants, the Narrative of the Life of Frederick Douglass (1845), The Confessions of Nat Turner (1831), and Incidents in the Life of a Slave Girl (1861) have been chosen for my thesis to analyze, focusing on slaves' characters as well as the impact slavery and colonialism have left on their minds and consciousness. Beforehand, we need to define the term "consciousness," as it is not limited to the dictionary definition of a person's awareness. Rather it encompasses how the person places themselves in the world, views their rank among other citizens of the world, and perceives and builds their understanding of the world. The constructs they build in turn impact and/or shape the person's relationships, interactions, sense of entitlement and rights, as well as self-esteem and self-worth. The oppression that silenced the slaves during those times helped them find an outlet for their voice through writing narratives. Therefore, the aforementioned narratives will serve as material for analysis of the impact of slavery from the perspective of African Americans to counter the impact that white supremacy and oppression have left on the perspectives of other writings or historical documents.